Website Design For Sdit Insan Madani, Bengkulu City - Rupawan Azzahra; Indra Kanedi; Venny Novita Sari (Jurnal Media Computer Science, 2026)
The rapid advancement of information and communication technology has encouraged various sectors, including education, to adapt in terms of information dissemination. SDIT Insan Madani of Bengkulu City, as an Islamic educational institution, still faces obstacles in promotion and information dissemination, which has so far been done manually. Therefore, this study aims to design and develop a school website as an effective and efficient medium for information and promotion. The system development method used is the waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance. The website was developed using PHP as the programming language and MySQL as the database. The main features of this website include registration information, school activities, student achievements, subject data, and school agendas. The result of this study is an online-accessible school website that helps the institution deliver information quickly, accurately, and efficiently. It is expected that the system will improve the quality of information services and support the school's digital promotion efforts.